Filipino children's favorite stories - Romulo, Liana; De LeoI?n, Joanne ([Hong Kong] Periplus North Clarendon, VT Distributed by Tuttle Pub., 2000)
"A collection of well-loved myths and tales from the Philippines. Many of the tales have been told by mothers to children over the centuries and cover classic childhood themes, such as the forces of good versus evil, children versus adults, the weak versus the strong, and others. While some of the stories have been retold and printed in many variations, others have never been published before"--Jacket.
Why mosquitoes buzz around our ears -- The terrible giant -- The hermit and the two worms -- The battle of the wind and the rain -- Alunsina -- A feast of gold -- The runaways -- The magic lake -- The deer and the snail -- A bridge of flowers -- Why the cock crows -- The battle of the sea and sky -- The Prince's bride.
Includes bibliographical references (p. 94)
Keywords: Legends -- Philippines; Tales -- Philippines; Mythology, Philippine; Folk literature, Philippine; Mythology, Philippine; Folklore -- Philippines